Helminth Eggs Parameter of Water Spinach Agriculture Field in Bandung - Mayrina Firdayati; Peni Astrini Notodarmojo; Barti Setiani Muntalif; Didit Trihartomo; Inat Shani Fathuna; Kiki Somantri (Universitas Trisakti, 2018)
The high prevalence of helminth infection in Indonesia had encouraged the government to issue the Regulation of the Minister of Health concerning the Prevention of Soil-transmitted Helminths in 2017. Researches on the presence of helminth eggs in the environment, in soil and water as a media for transmitting the disease, are very few. Aim: The aim was conducted to investigate the potential presence of helminth eggs causing STH infections in two urban agricultural areas in northern and southern part of Bandung City. Methodology and results: Samples of water from the inlet and plantation area, as well as soil and water spinach produced by both regions, were collected and analyzed for the presence of helminth eggs using modified Bailinger methods. The number of helminth eggs of 1–119 eggs/L in water, soil, and vegetable samples. Conclusion, significance, and impact study: The results confirmed that the irrigation water used in both areas has been contaminated by feces. The average number of fecal coli exceeds the allowable value for the irrigation water source based on the Grade 4 of water quality criteria in Indonesia. Variations in the number of helminth eggs found in the samples can be caused by environmental conditions such as temperature, humidity, and soil types. The presence of helminth eggs in irrigation water and land samples exceeds the value recommended by WHO (2006) in the guidelines for the safe use of wastewater for agriculture. It can lead to an increased risk of helminth infection to consumers, agricultural workers, as well as residents around the farmland.